RIGHT OF EXPRESSION IN PERGUB D.I YOGYAKARTA NUMBER 1 YEAR 2021PERSPECTIVE SIYASAH DUSTURIYYAH - Siagian, Siti Saadah (IBN KHALDUN BOGOR, 2022)
The Government of the Special Region of Yogyakarta issues and stipulates the Governor's Regulation (Pergub) DIY Number 1 of 2021 concerning implementing Public Expression of Opinions in Open Space. Article 5 of the Pergub reads that